The Integration of Governance Theory in the Development of Equitable Legal Policies - Safaruddin Harefa (CV. Austronesia Akademika, 2025)
This study addresses the limitations of state-centric legal systems in responding to increasingly complex social, political, and institutional challenges, which often result in legal policies that are formally valid but substantively unjust. It aims to explain how the systematic integration of governance principles can strengthen the legitimacy, fairness, and effectiveness of legal policymaking. Employing a normative juridical method, the research analyzes legislation, policy documents, jurisprudence, and scholarly works using statute, conceptual, and comparative approaches to examine how transparency, participation, accountability, and the rule of law are embedded in the formulation and implementation of legal policies. The findings show that when governance principles guide lawmaking, legal policy shifts from a unilateral exercise of state authority to a participatory and collaborative process involving multiple actors, thereby enhancing legal certainty, protecting public interests, and promoting social justice. The analysis also reveals that governance based mechanisms such as public consultation, judicial review, independent oversight bodies, and open-data regulations help reduce principal agent problems, curb corruption risks, and align legal outcomes with societal expectations. The study concludes that legal systems are better able to meet societal needs, maintain public trust, and support equitable development when governance principles are consistently institutionalized throughout the policy cycle, from agenda setting and drafting to implementation and evaluation, positioning governance theory as a foundational paradigm for designing responsive, accountable, and sustainable legal frameworks.